'He is Father Christmas when Man-U wins': EUFA league and the dynamics of spousal relations in Nigeria. (2nd January 2017) - Tade, Oludayo
Abstract : The European Champions League and Premiership have become infectious to Nigerian families. As a patriarchal society, husband fanship influences and alters social interactions before, during and after UEFA matches. Against this background, this paper examines the influence of husbands' sports fandom on social relations in families and opportunity for deviant behaviour. Findings show that husbands' identification with European clubs is redefining social relationships at the family level. Families were labelled as: couple as fans of same club, couple as fans of rival clubs and families with one soccer-loving partner. Loss of matches may lead to refusal to eat food, aggressive behaviour, conflict, lack of communication, while victory brings joy, gifts and better bonding and communication. Watching matches outside the home increases the opportunity of husbands to associate with deviant peers and, consequently, deviant behaviour. To keep their marriages, women have converted to soccer lovers to enhance communication and check their husbands' association with deviant peers.